2009
DOI: 10.1158/1055-9965.epi-09-0883
|View full text |Cite
|
Sign up to set email alerts
|

Does Film Smoking Promote Youth Smoking in Middle-Income Countries?: A Longitudinal Study among Mexican Adolescents

Abstract: Objective To determine whether exposure to smoking imagery in films predicts smoking onset among never-smoking Mexican adolescents. Methods The analytic sample was comprised of 11- to 14-year old secondary school students who reported never having tried smoking at baseline, 83% (1741/2093) of whom were successfully followed up after one year. Exposure to 42 popular films that contained smoking was assessed at baseline, whereas smoking behavior and risk factors were assessed at baseline and follow up. Logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 36 publications
(53 reference statements)
1
53
0
7
Order By: Relevance
“…Studies have shown that media images of smoking, particularly in movies, are linked to smoking and smoking initiation among adolescents. [35][36][37][38][39][40] Therefore, media literacy-or the ability to analyze and evaluate media messages 41 -has been proposed as a tool to better interpret media messages related to smoking, potentially influencing attitudes towards smoking and smoking behavior. Prior studies have shown an association between the level of smoking media literacy and smoking status among adolescents in the USA and in Jujuy, Argentina, as well as in US college students.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that media images of smoking, particularly in movies, are linked to smoking and smoking initiation among adolescents. [35][36][37][38][39][40] Therefore, media literacy-or the ability to analyze and evaluate media messages 41 -has been proposed as a tool to better interpret media messages related to smoking, potentially influencing attitudes towards smoking and smoking behavior. Prior studies have shown an association between the level of smoking media literacy and smoking status among adolescents in the USA and in Jujuy, Argentina, as well as in US college students.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding findings from other countries, effects similar to those in the US were found in Mexico, albeit somewhat weaker (Thrasher et al, 2008(Thrasher et al, , 2009. In Egypt significant effects were found only for boys (Islam & Johnson, 2007), in Germany (Hanewinkel & Sargent, 2007) and the United Kingdom (Waylen et al, 2011) similar effects as in the US were revealed, while studies from Scotland (Hunt et al, 2009(Hunt et al, , 2011 have produced conflicting results.…”
Section: Differences In the Effect Of Exposure To Smoking In Movies Amentioning
confidence: 73%
“…Smoking-related variables included smoking status of parents (any smoker vs none), siblings (any smoker vs none) and five closest friends (any smoker vs none). We also included sensation seeking, which is a robust predictor of smoking behaviour, including in Latin America,38 and has also been associated with marketing receptivity 39…”
Section: Methodsmentioning
confidence: 99%